AB0940 BIOMARKERS IN THE DIAGNOSIS OF ACUTE HOT JOINTS: AN EVALUATION OF RESEARCH INTEREST 1960-2018. (2nd June 2020) - Dey, M.; Al-Attar, M.; Peruffo, L.; Wilson, I.; Zhao, S. S.; Duffield, S.; Goodson, N.
Abstract : Background: The acute hot joint presentation is a common clinical emergency, often the result of crystal arthritis or trauma. However, all diagnoses can mimic septic arthritis, which should be excluded promptly due to the potential for rapid joint destruction and significant morbidity. The gold-standard test for septic arthritis is synovial fluid culture, which can take several days to perform. Meanwhile, patients are often admitted and given antimicrobials. Other specialties have made use of rapid biomarkers to exclude infection, for example, exclusion of empyema using pleural fluid pH and glucose [1]. Such biomarkers could reduce the need for lengthy hospital admissions and inappropriate antibiotic use in the acute hot joint presentation. Objectives: 1.Evaluate research interest over time, on the use of diagnostic biomarkers in the acute hot joint presentation. 2.Compare research interest in the use of diagnostic biomarkers in acute hot native versus acute hot prosthetic joints. Methods: We performed a review of the number of publications reporting the use and diagnostic accuracy of biomarkers to exclude infection in the acute hot joint presentations. The database, Scopus, was searched for English-language studies (1946-2018) using search terms relating to septic arthritis, crystal arthritis, and diagnostic markers derived from synovial fluid/aspirate. The number of papers published per year on prosthetic joints only was also calculated. Therefore, the following were recorded for each year 1946-2018: total number of studies; prosthetic joints only; native joints only. Values were plotted, with polynomial trend-lines and R 2 calculated. Results: Our search yielded 2279 relevant studies in total (561 on prosthetic joints), published 1946-2018. Only 1 study was identified for the year 1946; the next recorded publication was in 1960. Therefore, this single study was excluded as an outlier. Results are presented in Figure 1 . The number of studies on diagnostic biomarkers for acute hot joints continued to increase after 1960. From 2016, the number of studies conducted in prosthetic joints outnumbered those done in native joints. Polynomial trend-lines applied to the results showed studies on native acute hot joints are predicted to decline, while those in prosthetic joints will continue to increase. Conclusion: Reasons for an increasing number of studies on prosthetic compared to native acute hot joints include a narrower differential diagnosis in prosthetic joints, i.e. septic vs aseptic. In contrast, native acute hot joints may be the result of various causes including crystal arthritis, inflammatory arthritis, and trauma. Having a narrower differential diagnosis may facilitate diagnostic research in prosthetic joint presentations. Furthermore, incidence of prosthetic joint infection is also greater than that of native joint infection [2]. Nonetheless, the incidence of native joint infection is increasing [3]. This, and the lack of methods by which to rapidly distinguish native joint septic arthritis from non-infective causes, indicates that more research is required in this area. References: [1]Heffner JE et al. Pleural fluid chemical analysis in parapneumonic effusions. A meta-analysis. Am J Respir Crit Care Med. 1995 Jun;151(6):1700–8. [2]Roerdink RL et al. The difference between native septic arthritis and prosthetic joint infections: A review of literature. J Orthop Surg (Hong Kong). [3]Rutherford AI et al. A population study of the reported incidence of native joint septic arthritis in the United Kingdom between 1998 and 2013. Rheumatol (United Kingdom). 2016;55(12):2176–80. Disclosure of Interests: None declared